Targeted fiscal policy to increase employment and wages of unskilled workers - Konstantinos Angelopoulos; Wei Jiang; James R. Malley (University of Kent, School of Economics, 2017)
We extend the canonical model of search and matching frictions by including capital-skill complementarity in production, labour markets with skilled and unskilled workers and on-the-job-learning (OJL) within and across skill types. These extensions capture key characteristics of skilled and unskilled labour markets in the data. We find that increases in public spending to enhance unskilled productivity via OJL are beneficial to employed unskilled workers and reduce earnings inequality between employed skilled and unskilled labour. However, unskilled unemployment and labour income inequality within the group of unskilled labour rises. We next find that vacancy subsidies work to increase employment and returns to unskilled workers. However, unemployment for skilled workers rises and skilled wages and labour income fall in the short-run. We finally show that it is possible to increase skilled vacancy subsidies to nullify the negative effects on skilled employment following an increase in unskilled vacancy subsidies.
Keywords: E24; E32; J63; J64; J68; 330; fiscal policy; sectoral labour productivity; earnings inequality; search and matching